2021
DOI: 10.1089/thy.2020.0388
|View full text |Cite
|
Sign up to set email alerts
|

Liothyronine Use in Hypothyroidism and its Effects on Cancer and Mortality

Abstract: Background: The prescription of liothyronine (LT3) to treat hypothyroidism is increasing worldwide; however, the long-term safety of LT3 use has yet to be determined. Previous studies have suggested a possible association between LT3 use and breast cancer. The aim of this study was to examine the effects of LT3 use on cancer incidence and mortality. Methods: Our sample included the full adult population of individuals living in Sweden with at least three purchases of thyroid hormone therapy between July 2005 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 38 publications
0
10
0
1
Order By: Relevance
“…Well-designed randomized clinical trials in patients with persistent symptoms after exclusion of comorbidities are required to address this issue. Although our recent large register-based study ( 21 ) provided reassuring evidence regarding the risk of cancer and mortality in L-T3 treated Swedish patients, there could still be other health risks associated with long-term L-T3 therapy warranting randomized trials examining the safety of the combined treatment. Moreover, the cost-effectiveness of the combined treatment also remains an issue, as it is more expensive than L-T4 treatment alone ( 47 ) and usually requires more frequent monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Well-designed randomized clinical trials in patients with persistent symptoms after exclusion of comorbidities are required to address this issue. Although our recent large register-based study ( 21 ) provided reassuring evidence regarding the risk of cancer and mortality in L-T3 treated Swedish patients, there could still be other health risks associated with long-term L-T3 therapy warranting randomized trials examining the safety of the combined treatment. Moreover, the cost-effectiveness of the combined treatment also remains an issue, as it is more expensive than L-T4 treatment alone ( 47 ) and usually requires more frequent monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of randomized controlled trials have studied the effect of combined L-T4+L-T3 and five systemic reviews/meta-analyses have concluded that the combined treatment is not superior to standard L-T4 treatment with respect to hypothyroid symptoms and quality of life (15)(16)(17)(18) or patient preference (19). Data on long-term safety are limited (20,21). Therefore, European guidelines restrict the recommendation of L-T3 to that of experimental treatment (2).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies lasting 9 to 17 years found no increased risk of cardiovascular disease, atrial fibrillation, or fractures in patients using T3 compared to patients using T4 [ 87 , 88 ]. The use of LT3 did not lead to increased breast cancer or any cancer incidence and mortality compared with LT4 use [ 89 ]. There was only an increased incident use of antipsychotic medication during follow-up in T3 users [ 87 ].…”
Section: How To Make Progress In the Management Of Persistent Symptoms On Lt4 Despite A Normal Tsh?mentioning
confidence: 99%
“…In a long-term cohort study conducted in Sweden, the use of LT3 did not lead to an increase in the incidence of breast cancer, the incidence of any cancer, and all-cause mortality compared to the use of LT4. Surprisingly, there was evidence of lower mortality in LT3 users after dose adjustment, which was potentially attributed to an artifact of the underlying associations between dose and patient diagnosis [37].…”
Section: Candidates For Combined Levothyroxine + Liothyronine Therapymentioning
confidence: 94%